Radiation Oncologists' Approach to Internal Mammary Lymph Node Radiotherapy in Breast Cancer: The Turkish Society for Radiation Oncology Breast Cancer Study Group (TROD 06-005 Survey Study) - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2021)
Background: This study aimed to examine the practice patterns of radiation oncologists in Turkey regarding radiotherapy to the regional lymph nodes, including internal mammary lymph nodes (IMNs), and identify the factors influencing their clinical decisions in breast cancer patients. Methods: A nationwide, 19-point questionnaire was sent to the physician members of the Turkish Society for Radiation Oncology (TROD). Results: In total, 165 radiation oncologists completed the survey, corresponding to a 27% response rate. Regional radiotherapy was used in 64.2% of the patients with 1-3 axillary lymphatic involvement and unfavorable prognostic factors. In contrast, 61.2% of the respon-dents indicated that IMN should be included in the target volume for regional radiotherapy when the patient had one positive node after axillary lymph node dissection (ALND) in the inner quadrant and central region tumors. However, 71.5% of the respondents chose to include the IMN in the non-inner quadrant and non-central region tumors for patients with four or more positive nodes after ALND. The decision to offer internal mammary lymph node radiotherapy (IMNRT) varied widely and significantly among respondents, years in practice, and the rates of dedicating their clinical time to patients with breast cancer. Conclusion: The results of this survey revealed significant national variation in attitudes regarding the treatment of IMN. Thus, this study may also help document the impact of future studies on clinical practice.
Keywords: survey; breast cancer; internal mammary lymph nodes; regional nodal irradiation; radiotherapy; DBCG-IMN; IRRADIATION; COHORT; CHAIN